Learning Reading Beam No Tation Using Pianika Musical Instrumen For College Students Semester 1 Music Educations UNWIRA Kupang - Yunita Indriani Banfanu; Margareta Sofyana Irma Kaet; Flora Ceunfin (Universitas Muhammadiyah Enrekang, 2025)
This study examines learning to read sheet music using the pianica instrument for first semester students of the Music Education Study Program, UNWIRA Kupang, who generally do not have this ability well. The main objectives of this study are to: 1) Determine the process and results of learning to read sheet music. 2) Analyze the difficulties experienced by students in this learning and how to overcome them. In this study, ten meetings were conducted, which included the delivery of materials, etude practice exercises, and practice reading the song